Australian Enterococcal Sepsis Outcome Progamme, 2011 - Coombs, Geoffrey; Pearson, J.; Daley, D.; Le, T.; Robinson, J.; Gottlieb, T.; Howden, B.; Johnson, P.; Bennett, C.; Stinear, T.; Turnidge, J. (2014)
From 1 January to 31 December 2011, 29 institutions around Australia participated in the Australian Enterococcal Sepsis Outcome Programme (AESOP). The aim of AESOP 2011 was to determine the proportion of enterococcal bacteraemia isolates in Australia that are antimicrobial resistant, with particular emphasis on susceptibility to ampicillin and the glycopeptides, and to characterise the molecular epidemiology of the Enterococcus faecalis and E. faecium isolates. Of the 1,079 unique episodes of bacteraemia investigated, 95.8% were caused by either E. faecalis (61.0%) or E. faecium (34.8%). Ampicillin resistance was detected in 90.4% of E. faecium but not detected in E. faecalis. Using Clinical and Laboratory Standards Institute breakpoints (CLSI), vancomycin non-susceptibility was reported in 0.6% and 31.4% of E. faecalis and E. faecium respectively and was predominately due to the acquisition of the vanB operon. Approximately 1 in 6 vanB E. faecium isolates however, had an minimum inhibitory concentration at or below the CLSI vancomycin susceptible breakpoint of = 4 mg/L. Overall, 37% of E. faecium harboured vanA or vanB genes. Although molecular typing identified 126 E. faecalis pulsed-field gel electrophoresis (PFGE) pulsotypes, more than 50% belonged to 2 pulsotypes that were isolated across Australia. E. faecium consisted of 73 PFGE pulsotypes from which 43 multilocus sequence types were identified. Almost 90% of the E. faecium were identified as clonal complex 17 clones, of which approximately half were characterised as sequence type 203, which was isolated Australia-wide. In conclusion, the AESOP 2011 has shown that although polyclonal, enterococcal bacteraemias in Australia are frequently caused by ampicillin-resistant vanB E. faecium.